Microfinance Banks and Micro, Small and Medium Enterprises (MSMEs)Performance: The Implications of Micro Saving Habit Among Owners in Federal Capital Territory, Abuja, Nigeria - Song, Muru Bitrus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The study examined the implication of saving habit on MSMEs’ performance in Federal Capital Territory, Abuja, Nigeria. Thereafter, four-hundred MSMEs owners were sampled in the study areas using the Yamane (1967) in the six Area Councils of Abuja. Also, the descriptive statistics and Logit regression technique were used. From the descriptive statistics analysis, 94.6% sampled respondents fall within the economic active age; female (60.5%) and male (39.5%). Furthermore, large number of sampled respondents realized more than the monthly minimum wage of 70,000 naira; hence, they are considered economically averagely okay. The logit regression estimate showed that micro saving, loans from family members, loans from other sources and age of the respondent were significant and directly related to growth of MSMEs; while, loans from commercial banks was significant and indirectly related to growth of MSMEs at 5%significant level. Suggesting that having a daily, weekly, monthly or yearly saving with microfinance banks within the Federal Capital Territory, Abuja goes a long in contributing to growth of MSMEs. The study concluded that saving habit among MSMEs either on a daily basis, weekly, monthly or yearly with microfinance banks promote their creditworthiness, which boost MSMEs’ performance. Therefore, recommended that that MSMEs’ owners should ensure fully compliance with microfinance saving rule by not defaulting on their respective saving method pattern. Also, each MSMEs’ owners also should adopt a suitable saving pattern, which can also be on a daily basis, weekly, monthly or yearly